THE EFFECT OF MURABAHAH AND MUSYARAKAH FINANCING ON NET PROFIT AT INDONESIAN SHARIA BANK: akuntansy syariah - Azkia Harisatul; Wirman (Prodi Ekonomi Syariah Universitas Majalengka, 2022)
The purpose of this research is to find out how much influence murabahah and musyarakah have on net income at Bank Syariah Indonesia. This study uses multiple linear regression analysis assisted by the SPSS 16 application program. The population of this study is 36 months of monthly reports at Bank Syariah Indonesia for the periode 2018-2020. The research method used in this research is using multiple linear regression analysis. The results of this study that have been examined are the t arithmetic value of 3.577 < t table 2.03452 and the significant value of 0.001 < 0.05 then murabahah financing has an effect on net income, while the results of the t -.596 < t table 2.03452 and the significant value is .555 < 0.05 then musyarakah financing has no effect on net income. Then simultaneously the results of the calculated F value of 6.792 > t table 3.28 and the significance value 0.003 > 0.05 then murabahah financing and musyarakah financing affect net income.